1D/2D stormwater modelling to support urban flood risk management in estuarine areas: Hazard assessment in the Dafundo case study. Issue 4 (1st September 2020) - Cardoso, Maria Adriana; Almeida, Maria Céu; Brito, Rita S.; Gomes, João L.; Beceiro, Paula; Oliveira, Anabela
Abstract: Flood risk management in urban areas adjacent to the coast is essential to increase their resilience. This study aims at improving scientific knowledge of flood risk alongside estuaries, considering different hazards and integrating estuarine and urban drainage modelling. Mathematical modelling of stormwater systems is a useful tool to evaluate the susceptibility to flooding and identify potential measures to reduce flood risk. The assessment of urban drainage flooding uses a coupled 1D/2D model, applying 1D model to the underground system and 2D model for the surface component. Assessment scenarios were based on variables rainfall, estuarine water level, and degree of obstruction in sewers and at system outfalls. Estuarine hydrodynamics were simulated using the SCHISM‐WWM model. A web GIS platform was developed to support urban flood risk forecast and management providing urban analysis visualisation. The main objective is to forecast flooding in the Dafundo catchment supporting definition of population warnings. This paper proposes a flood risk assessment approach, using 1D/2D coupled modelling, estuarine hydrodynamics, integrating the assessment in a forecast web platform. The novelty is supporting an integrated flood risk management in stormwater systems, particularly in estuarine areas, providing an important improvement to assess flooding occurrence, regarding flood depth, area and duration.